2005
DOI: 10.1117/12.604821
|View full text |Cite
|
Sign up to set email alerts
|

Multi-timescale measurements of brain responses in visual cortex during functional stimulation using time-resolved spectroscopy

Abstract: Studies of neurovascular coupling (hemodynamic changes and neuronal activation) in the visual cortex using a timedomain single photon counting system have been undertaken. The system operates in near infrared (NIR) range of spectrum and allows functional brain monitoring to be done non-invasively. The detection system employs a photomultiplier and multi-channel scaler to detect and record emerging photons with sub-microsecond resolution (the effective collection time per curve point is ~ 200 ns). Localisation … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2007
2007
2010
2010

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 26 publications
(56 reference statements)
0
2
0
Order By: Relevance
“…Although initially this approach produced images with low spatial resolution, current methodology (based on the use of a large density of recording channels and of particular measurement procedures described in the section Materials and Methods ) has pushed the spatial resolution to a sub-cm level (Gratton and Fabiani, 2003 ). With this methodology, our group (Gratton et al, 1995 ; for a review, see Gratton and Fabiani, 2009 ), as well as others (e.g., Steinbrink et al, 2000 ; Wolf et al, 2002 ; Franceschini and Boas, 2004 ; Lebid et al, 2005 ; Tse et al, 2006 ; Kubota et al, 2008 ; Medvedev et al, 2008 ) have shown that fast optical signals can be recorded consistently, with a combination of spatial and temporal resolution that is adequate for the type of neuroimaging research considered above. However, other groups have questioned this possibility (Steinbrink et al, 2005 ; Radakrishnan et al, 2009 ).…”
Section: Introductionmentioning
confidence: 99%
“…Although initially this approach produced images with low spatial resolution, current methodology (based on the use of a large density of recording channels and of particular measurement procedures described in the section Materials and Methods ) has pushed the spatial resolution to a sub-cm level (Gratton and Fabiani, 2003 ). With this methodology, our group (Gratton et al, 1995 ; for a review, see Gratton and Fabiani, 2009 ), as well as others (e.g., Steinbrink et al, 2000 ; Wolf et al, 2002 ; Franceschini and Boas, 2004 ; Lebid et al, 2005 ; Tse et al, 2006 ; Kubota et al, 2008 ; Medvedev et al, 2008 ) have shown that fast optical signals can be recorded consistently, with a combination of spatial and temporal resolution that is adequate for the type of neuroimaging research considered above. However, other groups have questioned this possibility (Steinbrink et al, 2005 ; Radakrishnan et al, 2009 ).…”
Section: Introductionmentioning
confidence: 99%
“…Wolf et al ., 2000, 2003; Tse et al ., 2006; Tse & Penney, in press) and others using different methodologies (e.g. Steinbrink et al ., 2000; Franceschini & Boas, 2004; Lebid et al ., 2005; see Gratton et al ., 2006 for a comparison of different recording methods). By contrast, only one laboratory has reported inability to obtain a fast optical signal using photon time‐of‐flight measures (Syré et al ., 2003).…”
Section: Introductionmentioning
confidence: 99%